Report by Cuba on resolution 69/5 of the United Nations General Assembly entitled "Necessity of ending the economic, commercial and financial blockade imposed by the United States of America against Cuba (Government of Cuba CU, 2015)
Presents a brief synthesis of matters in relation to the application of the blockade from Apri 2014 to April 2015.
Keywords: FOREIGN RELATIONS